Credibility and obedience: memories of the Sheffield Industrial Mission - Atkinson, Mike H. (Theology, 2015)
This paper begins where I started my ministry in 1959, outlining the missionary nature of the Sheffield Industrial Mission from 1944 to 1966, and examines its missiological base and its problems with the Church of England’s hierarchy. It focuses particularly on the work of Bishops Leslie Hunter and Ted Wickham.